PERSEPSI LEMBAGA KESEJAHTERAAN SOSIAL ANAK TERHADAP PROGRAM BANTUAN YAPI MELALUI APLIKASI SIKS-GIS PADA DINAS SOSIAL KABUPATEN KARANANYAR - Ishak, Yanuar; Sutoyo, Sutoyo; Farida Sari, Ama (Prodi PPKn Universitas Slamet Riyadi, 2025)
This study aims to explore the perceptions of Child Welfare Institutions (LKSA) regarding the Orphan Assistance Program (YAPI), implemented through the SIKS-GIS application. A qualitative approach was employed, involving subjects such as Social Service officials, LKSA administrators, and children who benefit from the program. The focus of the research is on LKSA's perceptions of the SIKS-GIS application, with data collected through interviews and observations, and validated using source and method triangulation. The findings indicate that the YAPI program is well-received by orphaned children in Karanganyar, positively impacting their emotional well-being and daily needs. While the application facilitates access, challenges such as data overlap and technical issues persist. Keywords: Orphan Assistance, SIKS-GIS, Child Welfare Institutions (LKSA), Communication, Efficiency, Limitations, Ongoing Support